KEPEMIMPINAN ABU DAUD BEUREU’EH DALAM MEWUJUDKAN KEMERDEKAAN INDONESIA - Fajri, Heri; Putri Ismanita, Cut Nufus; Zaini, Muhammad (Jurnal Sosial Humaniora Sigli, 2023)
Abu Daud Beureu'eh was a cleric and politician who fought during the Dutch and Japanese colonial era until after Indonesian independence. This study aims to (1) analyze the history of Abu Daud Beureu'eh's leadership, (2) analyze the role of Abu Daud Beureu'eh in realizing independence and (3) analyze the leadership style of Abu Daud Beureu'eh who is described as a charismatic Acehnese cleric, respected by many people. The research method used is a qualitative research method that is historical in nature. Data collection techniques used are observation, interviews, literature studies and documentation in the form of documents related to the leadership role of Abu Daud Beureu'eh. The results of this study show that (1) the history of Abu Daud Beureu'eh's leadership in the world of politics and his position as a fighter had been proven before independence, he founded an organization in Aceh on May 5, 1939 called PUSA (All Indonesian Ulama Association) which aimed to bring together all ulama to have the same thoughts or understanding. The PUSA organization tried to implement and apply teachings in accordance with the teachings of the Qur'an and Hadith. (2) Abu Daud Beureu'eh played a very important role in the turmoil in Aceh, for example during the Dutch colonial era he led armed forces against the Dutch and Japanese who were colonizing Aceh in 1942 AD to 1945 AD, leading the mujahideen troops so that on September 1, 1947 Abu Daud Beureu'euh was appointed as the military governor of Aceh, Langkat and Tanah Karo with the rank of general manyor. On January 1, 1950 he was appointed as the governor of Aceh province. (3) Abu Daud had an extraordinary leadership style, namely military leadership style, charismatic leadership, autocratic leadership and democratic leadership. In his leadership Abu Daud was considered a tenacious cleric, Head of the Religious Affairs Office, military governor for the Aceh, Langkat and Tanah Karo regions, and the Supreme Advisory Council. Keywords: Role, Abu Daud Beureue'eh, Independence